Wideband fiber‐optic delay line with dynamic delay drift compensation. Issue 5 (May 2015) - Qi, Xiaoqiong; Xie, Liang; Wang, Hui
ABSTRACT: A wideband and high resolution fiber delay line system based on a self‐fabricated distributed‐feedback (DFB) laser is demonstrated in this article, where the delay time drift due to temperature variance is compensated using the extensibility of the standard single‐mode fiber (SMF). The DFB laser with the amplitude bandwidth of 18 GHz and the in‐band phase variance within 60° is applied as the optical source to provide wideband microwave signal delay. The temperature‐dependence delay variance is measured up to 42.8 ps/km/°C in SMF delay line. A compensation capability of 600 ps is reached with a fiber stretcher acted on a motor‐driven 300 m SMF. The proposed system not only provides delay drift compensation for the environmental‐sensitive systems, but also a feasible solution to realize continuously tuning of delay for stable systems. The tunable range of the microwave delay could be further extended using longer stretched fiber. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1219–1222, 2015